2013
DOI: 10.17772/gp/1634
|View full text |Cite
|
Sign up to set email alerts
|

SUVmax measured by 18F FDG PET/CT in the primary tumor in relations to clinical and pathological features of endometrial cancer

Abstract: Nowe techniki obrazowania stwarzają możliwości przedoperacyjnej oceny rozległości procesu nowotworowego. Pozytonowa emisyjna tomografia z zastosowaniem 18F-FDG zrewolucjonizowała obrazowanie onkologiczne w ostatnich latach, odgrywając kluczową rolę w diagnostyce wielu typów nowotworów. SUVmax (maximum standardized uptake valve) mierzony za pomocą 18F-FDG PET/CT jest półilościowym parametrem specyficznym dla PET, który związany jest z agresywnym zachowaniem się nowotworu.Cel pracy: Celem pracy była ocena przyda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Similarly. the obtained results agree with some investigations evaluating the relationship between SUV parameters and deep MI [45,46]. According to metabolic parameters, some groups suggested that MTV and TLG might be promising markers for LN involvement [47]; the present work corroborates this hypothesis, as MTV and TLG were the only parameters capable of discriminating and predicting LN metastases.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly. the obtained results agree with some investigations evaluating the relationship between SUV parameters and deep MI [45,46]. According to metabolic parameters, some groups suggested that MTV and TLG might be promising markers for LN involvement [47]; the present work corroborates this hypothesis, as MTV and TLG were the only parameters capable of discriminating and predicting LN metastases.…”
Section: Discussionsupporting
confidence: 91%
“…Chung et al [39] concluded that the median preoperative SUV max in cervical cancer was significantly higher in patients with higher FIGO stage, pelvic lymph node metastasis, parametrial involvement, large tumor size, presence of lymphovascular space invasion and deep cervical stromal invasion. Walentowicz-Sadłecka et al [40] also found that higher SUV max in endometrial cancer was significantly associated with high FIGO stage, deep myometrial invasion, high-grade and high-risk tumors. As a noninvasive method, SUV on 18 F-FDG PET/CT therefore seemed to be among the useful predictors for patients with carcinomas of the uterus before treatment.…”
Section: Discussionmentioning
confidence: 98%
“…There are controversies about whether the SUVmax value in the primary tumor differs in some prognostic factors. The mean SUVmax value in the primary uterine tumor grade III (2,3,6,7), advanced stage (III-IV) (2,6), deep myometrial invasion (6,7,8), cervical involvement (7) in patients with nodal metastasis (2,7) and large tumor size (≥4 cm) (3,8,9) was found to be significantly higher in patients with grade III (2,3,6,7), advanced stage (III-IV) (2,6), deep myometrial invasion (6,7,8), cervical involvement (7) in patients with nodal metastasis (2,7) and large tumor size (≥4 cm) (3,8,9). There are also studies that show that SUVmax values are not different in their presence and absence of some of the prognostic factors.…”
Section: Discussionmentioning
confidence: 99%